2019
DOI: 10.1002/jso.25524
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled descending branch latissimus dorsi mini‐flap in repairing partial mastectomy defect: Shoulder functional and esthetic outcomes

Abstract: Background The axillary‐approach pedicled descending branch latissimus dorsi (LD) mini‐flap presents clear benefits in repairing partial mastectomy defects. This study assessed the functional and esthetic outcomes of this flap compared with conventional breast‐conserving surgery (BCS). Methods From October of 2015 to March of 2017, patients with early breast cancer were enrolled and assigned to the LD group or conventional BCS (CCS) group according to the need of using the pedicled descending branch LD mini‐fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another study analyzing 174 patients using the Q-DASH scores showed that LDMF has a negative impact on shoulder function [ 12 ]. Although Zhou et al [ 13 ] showed no significant differences in muscle strength, shoulder range of motion, disabilities of the arm, shoulder, and hand scores between the LDMF and conventional BCS groups, the varied results may be due to the small number of patients analyzed in this study. The poor physical well-being experienced by patients after LDMF compared to that after TM in previous studies suggests that muscle damage and associated dysfunction could be a weakness of LDMF.…”
Section: Discussionmentioning
confidence: 57%
“…Another study analyzing 174 patients using the Q-DASH scores showed that LDMF has a negative impact on shoulder function [ 12 ]. Although Zhou et al [ 13 ] showed no significant differences in muscle strength, shoulder range of motion, disabilities of the arm, shoulder, and hand scores between the LDMF and conventional BCS groups, the varied results may be due to the small number of patients analyzed in this study. The poor physical well-being experienced by patients after LDMF compared to that after TM in previous studies suggests that muscle damage and associated dysfunction could be a weakness of LDMF.…”
Section: Discussionmentioning
confidence: 57%
“…Besides mastectomy and BCS, we noticed that 17 patients received breast reconstruction at the same time. Pedicled descending branch latissimus dorsi mini flap is used in BCS to guarantee a satisfactory cosmetic result, in the situation of extensively lesions, hematoma or far distance from lesion to Mammotome biopsy spot, that has been reported by our department previously (20,21). For those widespread diseases and diffuse microcalcifications, the nipple-areola complex and skin spared mastectomy combined with breast implants might be an appropriate alternative way.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study, Zhou et al compared shoulder morbidity in two groups: latissimus dorsi (LD) mini-flap vs. conventional BCS (depending on the need for replacement of volume) and found the LD mini-flap an excellent additional technique to conventional BCS according to shoulder morbidity ( 40 ). With a follow-up of 1 year, the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire was used, and an objective evaluation of range of motion (ROM) and muscle strength was made.…”
Section: Key Contents and Findingsmentioning
confidence: 99%